Promoting sustainable fishing practices - Mumbai Archive Project Team (Jio Institute, 2024)
The festival also serves as a platform to promote sustainable fishing practices and raise awareness about the importance of marine conservation. To set an example, in some stalls, food is served on banana leaves, an age-old Indian tradition which is environmentally friendly.